DIGITAL ACCOUNTING AND E-COMMERCE EMPOWERMENT: ENHANCING MILLENNIAL AND GEN Z MSME COMPETITIVENESS IN CULINARY SECTOR - Farah Faradesila; Zuraidah; Shalan, Amr Mohammed Mansoor (Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2025)
This study investigates the impact of digital accounting systems and E-commerce platforms on the competitiveness of Micro, Small, and Medium Enterprises (MSMEs) managed by Millennials and Generation Z, particularly in the culinary sector of Malang City. Although MSMEs are essential to Indonesia's economy, numerous enterprises still employ traditional approaches in financial administration and marketing. Due to the swift progression of technology, younger entrepreneurs, who are typically more digitally proficient, possess considerable potential to utilize solutions that enhance business efficiency and market competitiveness. Digital accounting entails the integration of technology into financial recordkeeping and analysis, allowing MSMEs to access real-time, accurate financial information that fosters greater transparency and operational efficiency. Simultaneously, E-commerce platforms provide MSMEs the opportunity to expand their market reach, reduce operational costs, and improve product exposure. The incorporation of these digital tools is expected to enhance MSMEs' competitiveness in the current rapid business landscape. A quantitative research methodology will be utilized, incorporating questionnairesaimed at proprietors of culinary MSMEs in Malang City, supplemented by interviews to obtain comprehensive insights into the advantages and challenges of digitalization. This study aims to elucidate the influence of digital technologies on MSME competitiveness and to guide entrepreneurs and policymakers in fostering MSME growth in the digital era. The findings are anticipated to enhance future academic study and bolster the local economic development of Malang City. This study applies samples from Malang city, a city in East Java, as the most developed culinary area in Indonesia. Other cities globally may take benefits from this study's results.